Wirkungen der Mindestlohnregelungen in der Gebäudereinigung - Gerhard Bosch; Thorsten Kalina; Claudia Weinkopf (Journal for Labour Market Research, 2012)
– The commercial cleaning industry is characterized by a high proportion of labour costs and a pronounced comparability and standardization of services. The statistical preconditions for the evaluation have not been ideal which is mainly due to the high proportion of part-time work and mini-jobs. The evaluation is based on a representative company survey, a survey of works counsellors, company case studies and micro-econometric calculations based on SIAB. The lower minimum pay rate for indoor cleaning tends to be the 'going rate' which otherwise might be undercut. Employees' protection has been improved by the more effective controls by the customs which are also assessed as very important for competition. Employment and working time volume have been increasing between 2000 and 2008 and the market share of the commercial cleaning industry has grown compared to cleaners in other industries. The micro-econometric analysis reveals all in all no negative impact on employment and suggests that the inclusion of the industry into the Law on the Posting of Workers (AEntG) might have led to shifts from mini-jobs to employment covered by social security.
Keywords: 330; Mindestlohn - Erfolgskontrolle; Gebäudereiniger; Beschäftigungseffekte; Wettbewerbsfähigkeit; Lohnhöhe; Tarifpolitik; Integrierte Arbeitsmarktbiografien; Beschäftigtenstruktur